2001
DOI: 10.1165/ajrcmb.24.1.4040
|View full text |Cite
|
Sign up to set email alerts
|

Triggering the Induction of Myofibroblast and Fibrogenesis by Airway Epithelial Shedding

Abstract: Myofibroblasts have been thought to participate in subepithelial fibrosis in asthma, but the mechanism of myofibroblast induction has not been fully understood. In this study we investigated injury-related myofibroblast induction in a coculture system of guinea-pig epithelial cells and fibroblasts cocultured in a human amnion chamber. After pseudostratified epithelial cells were mechanically scraped, migrated flat epithelial cells differentiated into cuboidal appearances on Day 4 and then returned to their ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 30 publications
1
105
0
2
Order By: Relevance
“…In another set of experiments we therefore evaluated whether human circulating fibrocytes can differentiate into myofibroblast-like cells under the influence of two fibrogenic cytokines, ET-1 and TGF-␤1, that fare known to function as important myofibroblast promoters (15,19,20,43,44) and are released in exaggerated quantities in the airways of asthmatic patients (30, 31, 40 -42). We found that fibrocytes cultured for 6 days in SFM alone were able to grow and constitutively produce fibronectin and collagen III with a pattern similar to mature lung fibroblasts (44,46).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In another set of experiments we therefore evaluated whether human circulating fibrocytes can differentiate into myofibroblast-like cells under the influence of two fibrogenic cytokines, ET-1 and TGF-␤1, that fare known to function as important myofibroblast promoters (15,19,20,43,44) and are released in exaggerated quantities in the airways of asthmatic patients (30, 31, 40 -42). We found that fibrocytes cultured for 6 days in SFM alone were able to grow and constitutively produce fibronectin and collagen III with a pattern similar to mature lung fibroblasts (44,46).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been proposed that myofibroblasts originate from airway resident cells, particularly tissue fibroblasts or myocytes (15)(16)(17)(18)(19)(20), there may be a circulating precursor still unidentified. Previous studies (21,22) have described a population of circulating cells, termed fibrocytes, that express fibroblast products as well as the hemopoietic stem cell Ag CD34, enter sites of tissue injury, and localize to areas of extracellular matrix deposition.…”
Section: Identification Of Circulating Fibrocytes As Precursors Of Brmentioning
confidence: 99%
See 3 more Smart Citations